Ultraviolet technology - an alternative to juice pasteurization - Rosnah, Shamsudin, Assoc. Prof.; Noranizan, Mohd Adzahan, Assoc. Prof. Dr.; Yap, Pui Yee (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org